2009
DOI: 10.1016/j.exger.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

On the enigma of carnosine’s anti-ageing actions

Abstract: Carnosine ( -alanyl-L-histidine) has described as a forgotten and enigmatic dipeptide. Carnosine's enigma is particularly exemplified by its apparent anti-ageing actions; it suppresses cultured human fibroblast senescence and delays ageing in senescence-accelerated mice and Drosophila, but the mechanisms reponsible remain uncertain. In addition to carnosine's well-documented anti-oxidant, anti-glycating, aldehyde-scavenging and toxic metal-ion chelating properties, its ability to influence the metabolism of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 107 publications
(89 reference statements)
0
46
1
2
Order By: Relevance
“…This conclusion is exemplified by carnosine's contrasting effects on tumour cells and differentiated fibroblasts (Hipkiss 2009a), whilst carnosine extends the proliferative potential of cultured human fibroblasts, lengthens their lifespan and suppresses the appearance of the senescent phenotype (McFarland and Holliday 1994), the dipeptide strongly inhibits the growth of cultured tumour cells, as outlined above. It is possible, however, to reconcile this apparent paradox when one considers the metabolic differences between these two cell types, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This conclusion is exemplified by carnosine's contrasting effects on tumour cells and differentiated fibroblasts (Hipkiss 2009a), whilst carnosine extends the proliferative potential of cultured human fibroblasts, lengthens their lifespan and suppresses the appearance of the senescent phenotype (McFarland and Holliday 1994), the dipeptide strongly inhibits the growth of cultured tumour cells, as outlined above. It is possible, however, to reconcile this apparent paradox when one considers the metabolic differences between these two cell types, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…A further interesting observation that may hint at a possible mechanism is the finding that some advanced glycation end products (AGEs) inhibit tumour growth (Bartling et al 2011). In fact, carnosine's ability to react with AGEs and many AGEinducing agents is one of its likely biological functions [for a recent review see (Hipkiss 2009a)]. Another aspect may be hidden behind carnosine's ability to scavenge reactive oxygen species (ROS) (Gorbunov and Erin 1991) [for review see (Guiotto et al 2005;Boldyrev et al 2007;Boldyrev 1993)].…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In addition to muscles, carnosine is also found in brains and hearts and is therefore suspected to be more than a buffering reagent in physiology (26 -30). Studies of carnosine have suggested that it has neuroprotective (31, 32), antiglycative (33), antioxidative (34), and anti-aging activities (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed to be an anti-glycation agent (for review, see Ref. 6) and a blood glucose regulator (7), whereas the dipeptide present in the olfactory system might be either a neurotransmitter or a neuromodulator (for review, see Ref. 8).…”
mentioning
confidence: 99%